Development of Android-based "NutriGuide" Application with Augmented Reality (AR) as Nutrition Education Media for Diabetes Patients at Tarogong Kidul Health Centre, Garut - Gin Gin Sugih Permana, Gin Gin Sugih Permana; Eva Daniati, Eva Daniati; Alvi Riansyah, Alvi Riansyah (Jurnal Medika Cendikia, 2025)
Type 2 diabetes mellitus (T2DM) is a global health problem that requires proper nutrition management. However, conventional nutrition education methods are considered less effective because they are static and less interactive. Type 2 diabetes mellitus (T2DM) has become a global health crisis with 537 million cases, where Indonesia ranks seventh in the world with 19.5 million sufferers, while in Garut Regency the prevalence reaches 12.3% due to a high-carbohydrate diet and low nutrition literacy. Overcoming the failure of conventional education that only has 20% knowledge retention after 3 months. This study aims to develop an Android-based "NutriGuide" mobile application that uses Augmented Reality (AR) technology to present nutrition information visually and interactively at the Tarogong Kidul Health Centre, Garut Regency. This research used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). A quasi-experimental design with a pre-test and post-test control group was employed to test the application's effectiveness. A sample of 60 respondents from the Tarogong Kidul Health Centre area was divided into an intervention group (n=30) using the NutriGuide app and a control group (n=30) receiving conventional education. Data were analyzed using univariate analysis and the Mann-Whitney test. The intervention group showed a significant increase in nutritional knowledge, with the median score rising from 9.5 to 14. In contrast, the control group showed minimal change, with a median score increase from 10 to only 10.5. Statistical analysis confirmed a significant difference in knowledge improvement between the two groups (p-value = 0.002). The Android-based "NutriGuide" application with AR technology is an effective and innovative medium for significantly improving nutritional knowledge among T2DM patients.